2008
DOI: 10.1359/jbmr.080613
|View full text |Cite
|
Sign up to set email alerts
|

Bone Resorption Inhibitor Alendronate Normalizes the Reduced Bone Thickness of TRPV5−/− Mice

Abstract: TRPV5 is a Ca 2+ -selective channel involved in transcellular Ca 2+ absorption expressed in kidney and in the ruffled border of osteoclasts. Studies in hypercalciuric TRPV5 knockout (TRPV5 −/− ) mice, which display significantly increased vitamin D levels, showed that TRPV5 ablation increases number and size of osteoclasts but impairs osteoclast-mediated bone resorption. The latter is not in line with the observed decreased bone thickness in TRPV5 −/− mice. Bisphosphonates also inhibit osteoclast-mediated bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 53 publications
0
25
0
1
Order By: Relevance
“…Anti-resorption drugs, such as bisphosphonates, selective estrogen receptor modulators, and hormone therapy have been used to treat osteoporosis for years. These agents suppress bone resorption and bone turnover, resulting in a relative increase of bone formation and bone mineral density and subsequently lowering fracture rates in hip and spine [7]. However, there seems to be limited information available with regard to the long-term usage of oral bisphosphonates.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-resorption drugs, such as bisphosphonates, selective estrogen receptor modulators, and hormone therapy have been used to treat osteoporosis for years. These agents suppress bone resorption and bone turnover, resulting in a relative increase of bone formation and bone mineral density and subsequently lowering fracture rates in hip and spine [7]. However, there seems to be limited information available with regard to the long-term usage of oral bisphosphonates.…”
Section: Introductionmentioning
confidence: 99%
“…103 Bindels et al demonstrated the role of Klotho in the regulation of TRPV5. [104][105][106][107][108][109][110] They also found that Klotho is expressed in high amount in kidney and co-localizes with TRPV5 (Fig. 3).…”
Section: Meeting Reportmentioning
confidence: 79%
“…showing that the number of resorption pits was reduced in TRPV5 (-/-) bone marrow cultures (Nijenhuis et al, 2008).…”
Section: Discussionmentioning
confidence: 96%